Efficacy of probiotics in patients with cognitive impairment: A systematic review and meta-analysis - Miaomiao Ma; Bo Li; Zhi Qu; Shejuan Liu; Sisi Li (PLoS ONE, 2025)
Objective To conduct an in-depth exploration of the specific impacts of probiotics and prebiotic supplements on cognitive impairment, it is imperative to also investigate pertinent factors, including the optimal dosage of probiotics for enhancing cognitive function. This investigation is essential for optimizing probiotic interventions to prevent and treat cognitive decline, aimed at preventing and aiding in the treatment of cognitive decline among patients with cognitive impairment. Methods A comprehensive computerized search was conducted across the Embase, PubMed, Web of Science, Cochrane Library, SinoMed, CNKI, Wanfang and WeiPu Data. Studies targeting randomized controlled trials (RCTs) were included. This search covered a timeframe extending from the inception of each database to September 2024. Following an independent process of literature screening, data extraction, and rigorous quality assessment conducted by two investigators, a meta-analysis was performed using Stata 15.0 software. Results A total of ten studies, involving 778 patients, were included in the analysis. The meta-analysis revealed that probiotics were effective in enhancing cognitive function among patients with cognitive impairment, with a standardized mean difference (SMD) of 0.52 (95% CI: 0.07, 0.98; P < 0.001). Subgroup analysis further demonstrated that the largest effect size was observed for studies utilizing the Mini-Mental State Examination (MMSE) scale as the outcome measure (SMD = 0.88). Additionally, the greatest efficacy was associated with single-strain probiotics (SMD = 0.81), and interventions lasting ≤12 weeks exhibited the most pronounced effect (SMD = 0.61). Conclusion Probiotics have been shown to enhance cognitive function, with a probiotic intervention program featuring a single probiotic strain and a duration of ≤12 weeks demonstrating particularly robust efficacy in improving cognitive function, as assessed by the MMSE scale.